LEADERSHIP STYLE AND COMMUNICATION PATTERNS OF ISLAMIC FOUNDATION LEADER IN MANAGING ORGANIZATIONS (Case Study At Tahfidz Abdurrahman Al-Fatih Bengkulu City) - Aditia, Rafinita (QAULAN: Journal of Islamic Communication, 2021)
The purpose of this study was to analyze and describe how the leadership style and communication patterns of Islamic foundation leader in managing organizations, especially in Tahfidz Abdurrahman Al-Fatih Bengkulu City. The method used in this research is a qualitative method. The type of research used is Field Research (field research) by directly visiting and seeking information directly from the situation where the research was conducted. Data collection in this study was carried out using interviews, observation, and documentation. From the research results, it was found that Ustad Ilham Rahmatun Putra as the leader of Tahfidz Abdurrahman Al-Fatih has his own leadership style and communication pattern in managing organization. Leadership Style which is owned by Ustad Ilham including including The Structuring Style, The Relinquishing Style, and The Equalitarian Style. By implementing these three leadership styles, Tahfidz Abdurrahman Al-Fatih grow and gain the trust of various parties. The communication pattern that occurs in Tahfidz Abdurrahman Al-Fatih is a wheel pattern, so that the leadership power is in a central position and is influential in the process of delivering the message where all running information must first be conveyed to the leadership. In addition, the message flow that occurs in an organizational network includes downward communication, upward communication, horizontal communication, and cross-channel communication.